Healthy Eating: Improve Nutrition with Food Stamps - Linda B. Bobroff (EDIS)
FCS8837, a 1-page fact sheet by Linda Bobroff, provides a brief overview of the USDA Food Stamps program for older adults. Includes a number for consumers to call if they think they may be eligible. Published by the UF Department of Family, Youth and Community Sciences, January 2007.